2021
DOI: 10.3390/app12010180
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Measurements of Zeta Potential in Fractured Lewisian Gneiss: Implications for the Characterization of Flow in Fractured Crystalline Bedrock

Abstract: Despite the broad range of interest and possible applications, the controls on the electric surface charge and the zeta potential of gneiss at conditions relevant to naturally fractured systems remain unreported. There are no published zeta potential measurements conducted in such systems at equilibrium, hence, the effects of composition, concentration and pressure remain unknown. This study reports zeta potential values for the first time measured in a fractured Lewisian gneiss sample saturated with NaCl solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 67 publications
3
5
0
Order By: Relevance
“…This finding is in good agreement with the result of Vinogradov, Hidayat, Kumar et al. (2022), where ζ was reported to be −10.52 and −10.69 mV, respectively.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This finding is in good agreement with the result of Vinogradov, Hidayat, Kumar et al. (2022), where ζ was reported to be −10.52 and −10.69 mV, respectively.…”
Section: Resultssupporting
confidence: 93%
“…The obtained values of the ζ are -11.8 mV and -12.0 mV for the confining pressures of 4 MPa and 7 MPa, respectively. This finding is in good agreement with the result of Vinogradov et al (2022a) where ζ was reported to be -10.52 mV and -10.69 mV, respectively.…”
Section: Comparison With Published Datasupporting
confidence: 92%
See 2 more Smart Citations
“…In this section the saturated effective excess charge density model Q^vREV,sat ${\hat{Q}}_{v}^{REV,sat}$ is confronted to experimental data. Note that only few studies reporting electrokinetic measurements on fractured material have been published in the literature (e.g., Moore & Glaser, 2007; Vinogradov et al., 2022). Therefore, we compare the prediction of our model with the coupling coefficient C c data obtained by Moore and Glaser (2007) for microcracked Sierra granite samples.…”
Section: Application Of the Model To Experimental Self‐potential Datamentioning
confidence: 99%